A Novel Pieszoelectric Thick-FIlm Free-Standing Cantilever Energy Harvester - Kok, Swee Leong; White, Neil; Harris, Nick (2008)
Research on energy harvesting from ambient vibration sources has been attracting tremendous attention recently. Free-standing piezoelectric structures are among the devices used as the energy harvester. The structures are commonly fabricated by using thin-film technology. However, their electromechanical properties are typically lower than those of thick-film materials. In this paper, a method of fabricating thick-film free-standing cantilevers, operated in d31 and d33 are described and the measurement results are presented. These devices are able to be operated at relatively low level of vibrations (frequencies below 500 Hz and acceleration levels below 10 m/s2) in ambient environment.